2020
DOI: 10.1021/acssuschemeng.0c07389
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrodenitrogenation of Pyridine under Hydrothermal Conditions: A Comprehensive Study

Abstract: This article focuses on the kinetic modeling and catalytic performance of hydrodenitrogenation of pyridine under hydrothermal conditions. Piperidine derivatives are the major nitrogen-containing intermediates, including 1-piperidinecarboxaldehyde, 1-piperidineethanol, and alkyl piperidines. Catalysts overall improved the formation of N-free products including 1-pentanol and 2-methyl-1-pentanol. Commercial Pd/C provided the highest pyridine conversion rate at 350 °C, while the homemade Ni–Ru bimetallic catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Except for the potential hydrogen source and promoter, water could serve as a reactant to produce hydrogen and alcohol, aldehyde, acid and other oxygen‐containing derivatives in the hydrothermal liquefaction of polyethylene to oil 43,44 . Similarly, Guo and Luo et al 45,46 also found H 2 O in the hydrothermal conditions could directly participate in hydrodenitrogenation reactions of nitrogen‐containing heterocyclic substances, in which the oxygen‐containing compounds were generated from the interaction with water.…”
Section: The Role Of Water For Co2 Hydrogenation In Hydrothermal Cond...mentioning
confidence: 99%
“…Except for the potential hydrogen source and promoter, water could serve as a reactant to produce hydrogen and alcohol, aldehyde, acid and other oxygen‐containing derivatives in the hydrothermal liquefaction of polyethylene to oil 43,44 . Similarly, Guo and Luo et al 45,46 also found H 2 O in the hydrothermal conditions could directly participate in hydrodenitrogenation reactions of nitrogen‐containing heterocyclic substances, in which the oxygen‐containing compounds were generated from the interaction with water.…”
Section: The Role Of Water For Co2 Hydrogenation In Hydrothermal Cond...mentioning
confidence: 99%
“…Our recent research has shown that FA, acting as a hydrogen source, can promote the HDN reaction of the nitrogen heterocyclic ring chemical pyridine under hydrothermal conditions with a Ni-Ru bimetallic catalyst. 14 Apart from an external hydrogen source such as H 2 and FA, high-temperature, high-pressure (HTHP) water (250-400 C, 5-25 MPa) itself is a potential hydrogen source as well because of its unique inherent property of high ionic product (K w ) and low dielectric constant. 15 In this case, H 2 could be in situ generated from the radical reaction under hydrothermal condi- 16 Wang et al 17 found that HTHP H 2 O can also act as a bridge for methanol activation and oxidation to produce in situ H 2 and thereby achieve HCO 3 À reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have demonstrated that H 2 O could serve as an environmentally benign solvent, it would introduce O into the biooil phase during hydrothermal HDN reactions. 14,18 Luo et al 19 pointed out two pathways to achieve HDN under hydrothermal conditions:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations